Study on characteristics of nitrification and denitrification of three small watersheds during wet and dry seasons under various sources of pollution: A case study of the Jinjing Basin - Tong, Lingling; Karim, Murni; M. Yusoff, Fatimah; Aris, Ahmad Zaharin; Abdullah, Ahmad Fikri; Liu, Feng; Li, Dejun; Puvanasundram, Puvaneswari (MDPI, 2024)
Nitrogen cycling in freshwater ecosystems is critical for maintaining water quality, and understanding the processes of nitrification and denitrification is essential for effective nitrogen management, particularly in areas with diverse pollution sources. This study investigated the nitrification and denitrification processes in three tributaries of the Jinjing River—Tuojia (agricultural), Jinjing (residential), and Guanjia (woodland)—during both the wet and dry seasons. The potential nitrification rates (PNRs) and potential denitrification rates (PDNRs) were measured across these sites. The highest rates were observed in Tuojia during the wet season, with the PNR reaching 39.7 µg·kg−1 h −1 and the PDNR reaching 3.25 mg·kg−1 ·h −1 , while the rates were considerably lower in Jinjing and Guanjia. The ammonia-oxidizing archaea (AOA) abundance was higher than the ammonia-oxidizing bacteria (AOB) abundance at all sites, with Tuojia exhibiting the highest AOA abundance (5.9 × 107 copies·g −1 ) during the wet season. The nitrate-nitrogen (NO3 −-N) content was a key factor influencing denitrification, and the AOA abundance was significantly correlated with nitrification rates (r = 0.69; p < 0.05). These findings highlight the spatial and seasonal variability in nitrogen cycling and emphasize the importance of developing targeted nitrogen management strategies in regions with mixed land uses and pollution sources.